2020
DOI: 10.3748/wjg.v26.i30.4442
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model for acute abdominal pain after transarterial chemoembolization for liver cancer

Abstract: BACKGROUND Transarterial chemoembolization (TACE) is the first-line treatment for patients with unresectable liver cancer; however, TACE is associated with postembolization pain. AIM To analyze the risk factors for acute abdominal pain after TACE and establish a predictive model for postembolization pain. METHODS From January 2018 to September 2018, all patients with liver cancer who underwent TACE at our hospital were included. General chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
2
10
2
Order By: Relevance
“…Therefore, high-quality external validation is required to verify the validity and generalisability of this prediction model in different populations. Second, some risk factors, which were demonstrated to contribute to postembolisation pain in previous studies, such as chronic liver disease and psychological factors, were not investigated in this research (3,9). Thus, future studies should develop a more robust prediction model that includes more potential contributing risk factors.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Therefore, high-quality external validation is required to verify the validity and generalisability of this prediction model in different populations. Second, some risk factors, which were demonstrated to contribute to postembolisation pain in previous studies, such as chronic liver disease and psychological factors, were not investigated in this research (3,9). Thus, future studies should develop a more robust prediction model that includes more potential contributing risk factors.…”
Section: Discussionmentioning
confidence: 90%
“…Among the malignant tumors with high morbidity and death rates, notably in Asia and Africa, is primary hepatocellular carcinoma (HCC) (1). According to reports, HCC is the second most frequent cause of cancer-related deaths in China and the sixth most frequent carcinoma (2,3). Most cases of HCC in China are already in the intermediate and advanced stages at diagnosis, precluding traditional radical surgery as an effective intervention (4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…TACE can increase the concentration of chemotherapy drugs exposed to tumors by injecting large doses of chemical drugs locally to the tumor target lesions, promoting tumor embolization infarction or necrosis [ 10 , 11 ]. Postembolic syndromes, including acute abdominal pain, nausea, and vomiting, are common after TACE, which is an important reason for prolonged hospital stay, decreased treatment effect, and interruption of treatment [ 12 ]. At present, clinical studies have reported that the incidence and severity of abdominal pain vary greatly in different cohorts of HCC patients after TACE treatment [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%